Edge computing in the automation of production processes - Duzhyk, Nataliia (My University, 2024)
Edge computing can provide more reliable hardware, reduce data processing time, and reduce data transfer costs, but expanding its use requires interoperability and standardization among the components of the edge computing architecture

Граничні обчислення можуть забезпечити більш надійне апаратне забезпечення, зменшити час обробки даних і зменшити витрати на передачу даних, але розширення їх використання вимагає взаємодії та стандартизації компонентів архітектури периферійних обчислень
Keywords: edge computing; industrial automation; data management strategies; периферійні обчислення; промислова автоматизація; стратегії управління даними; кафедра ділової іноземної мови та міжнародної комунікації